Water Management and NK Nutrition of Cucumber - SubbaRao R (Department of Agronomy, College of Agriculture, 1989)
An experiment was conducted at the Agronomic Research Station, Chalakkudy, during the summer season of 1984 (January to April) on water management and NK nutrition of cucumber (Cucumis sativus L.). It was laid out as a factorial experiment in split plot design with three replications. The main plot treatments consisted of nine combinations of three levels each of nitrogen and potassium, viz., zero, 50 and 100 kg/ha. The sub plot treatments consisted of four levels of irrigation, viz., cultivator’s practice of daily pot watering at the rate of 4 1/plant and irrigation to a depth of 5 cm at cumulative pan evaporation values of 25, 50, and 75 mm. The study revealed that cucumber responded well to frequent irrigations and higher levels of nitrogen and potassium. Growth characters like length of vine, number of leaves, leaf area index and dry matter production as well as yield components like mean length, girth, weight and number of fruits and fruit setting percentage were favourably influenced by one or more of the above factors. Only sex ratio showed a reverse trend for all the three factors. Fruit yield was also higher in frequently irrigated and well fertilized plots. Field water use efficiency was higher in the less frequently irrigated treatments and higher levels of nitrogen and potassium. Total consumptive use and Et/Eo values were maximum in 25 mm CPE irrigation treatment. Soil moisture depletion pattern showed that cucumber extracted as much as 60 per cent of the total water used from the top 30 mm soil layer. The nitrogen and potassium content of plants at all the stages of observation was enhanced by the application of the respective nutrients only. In general, composition of the respective nutrients only. In general, composition of major nutrients in plants was not affected by irrigation. The uptake of major nutrients was higher at higher irrigation frequencies and higher levels of nitrogen and potassium as in the case of dry matter production. Status of available nitrogen and potassium in the soil after the experiment was enhanced by the application of the respective fertilizers only. In general, irrigation had no influence on content of major nutrients in the soil. positive significant correlation with fruit yield was observed with growth characters (length of vine, number of leaves, leaf area index and dry matter production), yield attributing characters (mean length, girth, weight and number of fruits and fruit setting percentage) as well as uptake of major nutrients. Only sex ratio showed a negative correlation with yield. Irrigation at 25 mm CPE and application of 100 kg/ha each of nitrogen and potassium recorded the maximum profit, net return per rupee invested and benefit : cost ratio.